Validating and Adapting the Motivated Strategies for Learning Questionnaire (MSLQ) for STEM Courses at an HBCU - Caesar R. Jackson (SAGE Publishing, 2018)
This study investigated the validity and reliability of the Motivated Strategies for Learning Questionnaire (MSLQ) for minority students enrolled in STEM courses at a historically black college/university (HBCU). Confirmatory factor analysis was used to test the third-order factor structure and to respecify the model. An adequate fit to the study sample data was achieved for the respecified MSLQ (MSLQ-R), and measurement invariance was verified on four groups within the HBCU sample. The highest correlates with EOC grade on the MSLQ-R were self-efficacy, task value, effort regulation, and time and study environment. Metacognitive self-regulation and strategy use variables were found to not correlate with EOC grade. A useful capability to discriminate on the basis of academic performance was exhibited by the MSLQ-R.